2022
DOI: 10.3389/fneur.2022.945640
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed postoperative hyponatremia in patients with non-functioning pituitary adenomas undergoing transsphenoidal surgery: A single-institution study

Abstract: PurposeWe aimed to assess factors influencing the occurrence of delayed hyponatremia after transsphenoidal surgery (TSS) in patients with a non-functional pituitary adenoma (NFPA).MethodsWe retrospectively collected the clinical data of patients who underwent TSS for NFPA between January 2016 and January 2021. The pituitary region was preoperatively scanned with 3.0 T magnetic resonance imaging. The risk factors for delayed postoperative hyponatremia for NFPA were identified by univariate and multivariable log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Huang et al [15] demonstrated that preoperative hyperprolactinemia is an independent risk factor delayed hyponatremia following endoscopic transsphenoidal surgery for non-functioning pituitary adenomas. Our study shares a similar viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [15] demonstrated that preoperative hyperprolactinemia is an independent risk factor delayed hyponatremia following endoscopic transsphenoidal surgery for non-functioning pituitary adenomas. Our study shares a similar viewpoint.…”
Section: Discussionmentioning
confidence: 99%